PENGARUH LATIHAN QUICK LEAP TERHADAP EXPLOSIVE POWER OTOT TUNGKAI PADA TIM BOLA VOLI PUTRA JUNIOR PKDP PENBARU - Afnanda Rozi Fahlefi; Ramadi Ramadi; Ni Putu Nita Wijayanti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : The problem in this research was the lack of explosive power leg muscle in the athletes smash and block when doing smash and block, it was still not optimal or still low. This was evident when they exercised and competed, their smashed were in netted and out, moreover the blocks were not able to reach the ball, so the team got an attack from opponent team very easy. This research was conducted at the Junior male Volleyball Team PKDP Pekanbaru. The population in this research is the Junior male Volleyball Team PKDP Pekanbaru which consisted of 12 people. The exercises in this research was the Quick Leap. The type of research is an experiment research which aims to see the effect of the form of exercise. The sampling technique used total sampling, where the total population were as sample. The techniques of collecting the data derived from Pre-test and post-test. The Instrument research used Power Vertical Jump Test Test. The analyzes were performed by using t-test. Based on data analysis and discussion, as evidenced by Tcount was 6 and Ttable was 1.796. It means Tcount>Ttable. At levelɑ= 0.05. It can be concluded that there is a significant effect of exercise Quick Leap on Junior Male Volleyball Team PKDP Pekanbaru.Keywords: Quick Leap, Explosive Power of leg muscle.